Election Crimes - Razaq Abd, Wajna (Journal of College of Education, 2022)
Abstract Considering the legislator’s importance in protecting the political rights and freedom generally and the right to elect specifically, the Iraqi legislator dedicated through the election law and the criminal law the criminal liability toward all kinds of the election crimes and their figures whether they are derived from criminal intention or neglecting or because of the precede by any other part regarding those related to the election process or any individual in charge for the administrative organization. The election process entity is consisted from the elector, nominee and those who in charge for the election process are participating in the election process positively to succeed the elections and conducting the work positively regarding the law or their participation will be negatively through impediment the election process by violating the rules which lead to illegal results and negative consequences. The penalty codes were confirmed by the author, because without them we will not guarantee respect to all election legislations. The thought of election crimes were discussed by the election legislations for the election process. Also, false documents, stealing papers, bribe, breach of trust and others were mentioned in law text with all penalties. In this current paper, we have discussed the major gaps to confront the election crimes and how to avoid them or reducing their consequences to reduce the gap between the citizens and the politician who have the desire to reach the parliament through the election process and stay away as possible from problems and election violation such as; committing violations, bribes and election manipulation.